2020
DOI: 10.15376/biores.15.2.2839-2849
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of fungi inhabiting rubber-impregnated wood, and their role of quality changing the impregnated wood

Abstract: Knowledge of the types of fungi inhabiting wood, their growth conditions, and level of damage is needed to design an effective and efficient preservation process. Researchers have tried to identify fungi that play a role in attacking wood products (impregnated wood), including the type and the role of these fungi in changing the quality of processed wood. Isolation was completed on fungal-attacked wood. The first isolation resulted in approximately 26 isolates, which were then grouped into 8 groups based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…There is limited research on the mechanism of wood degradation by Fusarium ; however, F. solani is currently known to degrade cellulose and lignin, producing cellulase, Lac, LiP, and MnP ( Saparrat et al, 2000 ; Wu et al, 2010 ; Obruca et al, 2012 ). After being infected with F. solani , the cellulose and hemicellulose content in wood will decrease ( Rahmawati et al, 2020 ). Benaddou et al (2024) experiment revealed that F. oxysporum and F. solani were the most selective lignin-degrading fungi among the tested fungi.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited research on the mechanism of wood degradation by Fusarium ; however, F. solani is currently known to degrade cellulose and lignin, producing cellulase, Lac, LiP, and MnP ( Saparrat et al, 2000 ; Wu et al, 2010 ; Obruca et al, 2012 ). After being infected with F. solani , the cellulose and hemicellulose content in wood will decrease ( Rahmawati et al, 2020 ). Benaddou et al (2024) experiment revealed that F. oxysporum and F. solani were the most selective lignin-degrading fungi among the tested fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Karakterisasi sampel dilakukan dengan cara analisa proximate (berdasarkan standard ASTM E871, E872, D1102), analisa ultimate dengan Leco elemental analyzer (model Elementar vario macro cube dari Elementar Analysensysteme GmbH), serta pengukuran nilai kalor dengan bomb calorimeter (model C200 dari IKA-Werke GmbH & Co. KG). Analisa komposisi biomassa juga dilakukan dengan fraksionasi sekuensial menggunakan Metode Chesson [4] seperti yang dilaporkan oleh Rahniawati dkk [5]. Semua pengukuran dilakukan perulangan sebanyak tiga kali untuk akurasi analisa.…”
Section: Methodologiunclassified
“…and Aspergillus sp. were also identified from laminated veneer lumber (LVL) which is made from rubberwood (Rahmawati et al 2020), and buried archaeological woods that belonging to the genera Picea, Larix, and Pinus (Pedersen et al 2020). Based on the references, it was revealed that P. formosus or P. maximus as KrC 1, KrD 1, and KrD 2, and Penicillium crustosum as KrE 1 have not been isolated from rubberwood and stored in one of Indonesia's Cultural Collections, while Aspergillus from section Aspergillus as KrC 2 has been isolated and stored in one of the culture collections, but not derived from rubberwood.…”
Section: Phylogenetic Of Stain Fungimentioning
confidence: 99%